Japan Has developed Luxury Brands - Shin'ya Nagasawa (Marketing Review St.Gallen, 2016)
LVMH Moët Hennessy-Louis Vuitton SA is the world's largest luxury brand conglomerate. Although it is not widely known, it was Japanese consumers that developed the market for this luxury brand group. This paper will reveal the birth and developmental history of luxury brand conglomerates. This paper describes "Louis Vuitton and Japan in 1970s," "The Coming of Arnault, the leader of the 'Brand Empire,'" "Those who Own the Japanese Luxury Brand Market will Own the World," "Necessities for Success in Japan," "Japan's Luxury Product Distribution Network," "The Consumptions Behavior of the Wealthy Class: Freestanding Stores or Department Stores," and "Department Stores and Luxury" was invented in Japan.
Keywords: 650